ClassPoint to Classroom Learning Enhancement: An Interventional Tool Integrated in PowerPoint Presentations - Ananayo, Sharon (SEAMEO QITEP in Science, 2024)
This research investigated the effectiveness of interactive ClassPoint presentations in enhancing students’ engagement and understanding of Science concepts in Grade 8. A quasi-experimental design with a quantitative follow-up survey was employed in this study. The participants were the 50 Grade 8 students who were divided into control and experimental groups, each comprising 25 learners. The control group was exposed to regularly-used teaching modalities, including PowerPoint presentations. Meanwhile, the experimental group was employed with ClassPoint presentations. A pre-test/post-test was used to measure effectiveness, and a survey questionnaire was used to gather students’ feedback on ClassPoint. The gathered data was analysed using the Wilcoxon signed-rank test, Mann-Whitney U test, and Frequency distribution. Findings revealed that the utilisation of ClassPoint presentations has significantly improved the scores of the students and is a better teaching modality when compared to the other learning modalities used. In addition, over half of the students strongly agreed that ClassPoint has increased their motivation (64%) and their engagement in the class (56%). This feedback aligned with their strong agreement that lessons were lively and interesting (64%), andClassPoint’s display slides helped them to focus and follow the teacher’s presentation better (68%). Nearly half (48%) also found these activities helpful for self-reflection on their learning progress. These findings suggested that ClassPoint can be employed as an alternative learning strategy for Science 8.